Stable $t$-Structures and Homotopy Category of Strongly Copure Projective Modules (Communications in Mathematical Research, 2019)
In this paper, we study the homotopy category of unbounded complexes ofstrongly copure projective modules with bounded relative homologies $\mathcal{K}^{∞,bscp}(\mathcal{SCP})$.We show that the existence of a right recollement of $\mathcal{K}^{∞,bscp}(\mathcal{SCP})$ with respectto $\mathcal{K}^{–,bscp}(\mathcal{SCP})$, $\mathcal{K}_{bscp}(\mathcal{SCP})$ and $\mathcal{K}^{∞,bscp}(\mathcal{SCP})$ has the homotopy category ofstrongly copure projective acyclic complexes as a triangulated subcategory in somecases.
Keywords: homotopy category; recollement; stable $t$-structure